2014
DOI: 10.1371/journal.pone.0085485
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Fibroblasts Mediate Extracellular Matrix Remodeling and Invasion of Scirrhous Gastric Carcinoma Cells

Abstract: Scirrhous gastric carcinoma (SGC) has the worst prognosis of all gastric cancers, owing to its rapid expansion by invasion and frequent peritoneal dissemination. Due to the increased proliferation of stromal fibroblasts (SFs) that occurs within SGC lesions and the peritoneal metastatic sites, SFs have been proposed to support the progression of this disease. However, the biological and molecular basis and the pathological role of the intercellular interaction between SGC cells and SFs remain largely unknown. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 29 publications
(36 reference statements)
1
31
0
Order By: Relevance
“…These cancers, especially Borrmann 4 gastric cancers, are characterized by rapid cancer cell infiltration and proliferation, accompanied by extensive stromal fibrosis. Increased proliferation of stromal fibroblasts within scirrhous gastric carcinoma lesions and peritoneal metastatic sites suggests that stromal fibroblasts support the progression of this disease [43]. IgG4-RD is also characterized by a variable degree of fibrosis [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…These cancers, especially Borrmann 4 gastric cancers, are characterized by rapid cancer cell infiltration and proliferation, accompanied by extensive stromal fibrosis. Increased proliferation of stromal fibroblasts within scirrhous gastric carcinoma lesions and peritoneal metastatic sites suggests that stromal fibroblasts support the progression of this disease [43]. IgG4-RD is also characterized by a variable degree of fibrosis [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide new insights into how tumor cell-shed MVs can influence the microenvironment by promoting ECM reorganization. Specifically, we showed that MVs from cancer cells increased epithelial cell contractility, which is known to be required for ECM remodeling and reorganization (Alcoser et al, 2014; Yamaguchi et al, 2014). Interestingly, tumor shed MVs can also mediate the transformation of fibroblasts into cancer associated fibroblasts (Webber et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tumors in WT mice consisted of radially aligned collagen fibers with interacting tumor cells along them, suggesting a more invasive tumor microenvironment [37]. Mechanical remodeling of the ECM through increased contractility of CAFs was also observed in scirrhous gastric carcinoma (SGC) [38]. Co-culture of SGC cells and CAFs generated ‘invasive foci’ in Matrigel.…”
Section: Cafs Promote Cancer Cell Invasion By Modifying the Stromal Ecmmentioning
confidence: 99%
“…These invasive foci were comprised of CAFs, which reorganized the matrix through actin–myosin contractility, and cancer cells that surrounded the CAFs invaded into Matrigel. Interestingly, treatment with the myosin-II (MyoII) inhibitor blebbistatin significantly reduced the invasion of these foci, whereas treatment with the broad MMP inhibitor GM6001 did not perturb the matrix remodeling and invasion phenotype [38]. …”
Section: Cafs Promote Cancer Cell Invasion By Modifying the Stromal Ecmmentioning
confidence: 99%